Rotation of both X- and Y-axes is a predictive confounder of ulnar nerve injury and open reduction in pediatric lateral flexion supracondylar humeral fractures: A retrospective cohort study - Sun, Jun; Shan, Jing; Meng, Lian; Liu, Tianjing; Wang, Enbo; Jia, Guoqiang (Frontiers in Pediatrics, 2022)
Background Rotation of the distal fragment often occurs in flexion-type supracondylar humerus fractures (SCHFs), potentially leading to ulnar nerve injury (UNI) and open reduction. We analyzed the correlation between the rotations and UNI or open reduction and then assessed the risk factors associated with these rotations. Methods Data of Wilkins type III lateral flexion SCHFs were collected over a 10-year time period (1 January 2012 to 31 December 2021) in Children's Hospital of Fudan University Anhui Hospital. We defined the rotation of the distal fragment on the coordinate axis as two types, IIIA (X-axis rotation) and IIIB (the rotation of both X- and Y-axes) on X-ray radiography. Demographic data, the incidence of the two-type rotation, odds ratios (ORs) of UNI and open reduction, and risk factors of the rotation of both X- and Y-axes were analyzed. Results Totally, 152 patients were found (50 with IIIA vs. 102 IIIB). The UNI rate was 13%, and the open reduction rate was 22%. The UNI rate of the IIIB was five-fold higher than that of the IIIA [OR, 5.143; 95% confidence interval (CI), 1.414–23.125; p = 0.019], and the open reduction rate of the IIIB was nearly five-fold higher than that of the IIIA (OR, 4.729, 95%CI, 1.584–14.495; p = 0.003). In these two types, patients with UNI had a higher risk of open reduction than those without UNI (OR, 9.816; 95%CI, 3.503–27.508; p = 0.001). In the multiple regression analysis, a high level of fracture was identified as a risk factor for the rotation of both X- and Y-axes. Conclusion Type IIIB lateral flexion-type SCHFs have higher rates of UNI and open reduction, and a high level of fracture is a risk factor associated with this type.